2011
DOI: 10.1007/s10384-010-0886-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up results of photodynamic therapy for polypoidal choroidal vasculopathy

Abstract: Long-term visual outcomes were not good owing to the high frequency of recurrent polypoidal lesions, as well as enlargement and neovascular changes involving abnormal vascular networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 30 publications
0
39
0
3
Order By: Relevance
“…16,17 Although our study showed favorable results, the persistent abnormal vascular networks may indicate a high risk of recurrent polypoidal lesions. 12 In fact, IVR group showed higher recurrence rate compared with PDT group during the follow-up period. Therefore, more investigations are needed to assess the further long-term efficacy of IVR in patients with PCV.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…16,17 Although our study showed favorable results, the persistent abnormal vascular networks may indicate a high risk of recurrent polypoidal lesions. 12 In fact, IVR group showed higher recurrence rate compared with PDT group during the follow-up period. Therefore, more investigations are needed to assess the further long-term efficacy of IVR in patients with PCV.…”
Section: Discussionmentioning
confidence: 87%
“…[5][6][7][8][9][10] However, the long-term outcomes of PDT for PCV indicate that frequent recurrences often result in a visual acuity loss. [11][12][13][14] On the other hand, ranibizumab (Lucentis, Genentech, Inc., South San Francisco, CA, USA) is a recombinant humanized anti-vascular endothelial growth factor (VEGF) antibody fragment targeting all isoforms of VEGF 15 that has been used extensively for the treatment of AMD. The treatment of PCV using ranibizumab has also yielded promising results.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, longer follow-up studies of PDT of 2 or 3 years have reported that the VA decreased at the final visit. [24][25][26] It is well known that PDT cannot resolve the branching Figure 1 The diagram shows the retreatment criteria in the current study after month 3 (3 months after treatment). Followup examinations, including evaluation of the OCT images, were performed every month until month 24.…”
Section: Discussionmentioning
confidence: 80%
“…Золотым стандартом диагностики ПХВ является ан-гиография с индоцианином зеленым, однако ее проведе-ние сопряжено с риском осложнений, характерных для контрастных методов исследования [17][18][19][20].…”
Section: актуальностьunclassified